Contraceptives Knowledge and Use among Reproductive Aged Women from Squatters of Kathmandu, Nepal - Dhital, R; Shrestha, SM; Pradhan, PMS; Rajbhandari, AK (Nepal Journal of Obstetrics and Gynaecology, 2016)
Aims: This study aims to assess the knowledge and use of contraceptives and the associated factors among the married reproductive aged women residing in squatters of Kathmandu, Nepal. Methods: This descriptive cross sectional study was conducted in six squatter settlements of Kathmandu in February 2015. A total of 156 married reproductive aged women were included through convenient sampling. Descriptive statistics were summarized and bivariate logistic regression was performed. Results: A total of 80.7% had knowledge and 66.6% of women were currently using at least one modern contraceptives method. Injectable was most commonly used (58%) whereas condom was the least (3%). The women who were less than 35 years of age, having a child less than five years of age and women who were literate were more likely to have knowledge on contraceptives with (OR=2.609, p=0.011), (OR=5.579, p=0.025) and (OR=3.6, p=0.007) respectively. Similarly, women less than 35 years of age and women having last child less than five years of age were less likely to be using contraceptives currently with (OR=0.344, p=0.033) and (OR=0.397, p=0.01) respectively. Conclusions: This study showed the actual use was lower than the knowledge. Among the contraceptives used, condom usage was very low. Younger women and mothers with last child less than five years of age were less likely to use contraceptives. These results highlight the risk related to sexual and reproductive health in this vulnerable population.